2006
DOI: 10.1121/1.2173513
|View full text |Cite
|
Sign up to set email alerts
|

Vocal responses to unanticipated perturbations in voice loudness feedback: An automatic mechanism for stabilizing voice amplitude

Abstract: The present study tested whether subjects respond to unanticipated short perturbations in voice loudness feedback with compensatory responses in voice amplitude. The role of stimulus magnitude (±1,3 vs 6 dB SPL), stimulus direction (up vs down), and the ongoing voice amplitude level (normal vs soft) were compared across compensations. Subjects responded to perturbations in voice loudness feedback with a compensatory change in voice amplitude 76% of the time. Mean latency of amplitude compensation was 157 ms. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
117
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 28 publications
11
117
0
Order By: Relevance
“…Under feedforward control, task performance is executed from previously learned commands, without reliance on incoming task-related sensory information. Speech production involves both feedforward and feedback control, and auditory feedback has been shown to impact both control processes (Houde and Jordan, 1998;Jones and Munhall, 2005;Bauer et al, 2006;Purcell and Munhall, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Under feedforward control, task performance is executed from previously learned commands, without reliance on incoming task-related sensory information. Speech production involves both feedforward and feedback control, and auditory feedback has been shown to impact both control processes (Houde and Jordan, 1998;Jones and Munhall, 2005;Bauer et al, 2006;Purcell and Munhall, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the reflexive control of speech loudness appears to follow a time course similar to the response to pitch-shifted feedback, or the pitch-shift reflex (PSR) [4,9,49,72,73,136]. Speakers exhibit a reflexive compensatory response to perceived shifts in voice pitch which occurs with a latency of approximately 130 ms and, again, appears not to be under volitional control [4,9,72,73,136].…”
Section: Auditory Feedback In Normal and Disrupted Vocalizationsmentioning
confidence: 99%
“…This phenomenon, in which a speaker increases or decreases voice amplitude in response to perceived changes in voice loudness feedback, appears similarly reflexive but lends itself to more detailed analyses of the relative effects of amplitude, timing and speech context. For example, Bauer et al found that compensatory changes in voice amplitude exhibited the greatest relative gains in response to the smallest (1dB) perturbations in feedback loudness, and response magnitudes were larger for the soft voice amplitudes than for normal voice amplitudes [4]. Loudness compensation was greater for increases than decreases in feedback loudness, and the mean compensation latency was approximately 150 ms [4,49].…”
Section: Auditory Feedback In Normal and Disrupted Vocalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voice loudness perturbation paradigms have also been examined to investigate the online control of voice amplitude [4][5][6]. Perturbations were found to result in compensatory responses in voice amplitude with similar latencies as voice pitch feedback perturbations.…”
Section: Introductionmentioning
confidence: 99%